2015
DOI: 10.3390/ijms160818293
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Phytoestrogen Genistein in Modulating Acute Methotrexate Chemotherapy-Induced Osteoclastogenesis and Bone Damage in Rats

Abstract: Chemotherapy-induced bone damage is a frequent side effect which causes diminished bone mineral density and fracture in childhood cancer sufferers and survivors. The intensified use of anti-metabolite methotrexate (MTX) and other cytotoxic drugs has led to the need for a mechanistic understanding of chemotherapy-induced bone loss and for the development of protective treatments. Using a young rat MTX-induced bone loss model, we investigated potential bone protective effects of phytoestrogen genistein. Oral gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 60 publications
4
32
0
Order By: Relevance
“…The nonsignificant changes in trabecular spacing and trabecular thickness observed in this study are also consistent with findings of previous investigations (T. J. King et al, 2012;T. King et al, 2015;Xian et al, 2007), and MTX-induced reduction in BV/TV (%) corresponded with the decrease in trabecular number as described previously .…”
Section: Treatment Effects On Bone Loss and Bm Adipositysupporting
confidence: 93%
“…The nonsignificant changes in trabecular spacing and trabecular thickness observed in this study are also consistent with findings of previous investigations (T. J. King et al, 2012;T. King et al, 2015;Xian et al, 2007), and MTX-induced reduction in BV/TV (%) corresponded with the decrease in trabecular number as described previously .…”
Section: Treatment Effects On Bone Loss and Bm Adipositysupporting
confidence: 93%
“…The stained sections were then observed and photographed under a light microscope. The cell densities of osteoblasts or TRAP‐positive multinuclear osteoclasts lining the surface of trabecular bone were measured in the secondary spongiosa of proximal tibias and expressed as cells/mm 2 trabecular area …”
Section: Methodsmentioning
confidence: 99%
“…The cell densities of osteoblasts or TRAP-positive multinuclear osteoclasts lining the surface of trabecular bone were measured in the secondary spongiosa of proximal tibias and expressed as cells/ mm 2 trabecular area. (29) For bone histomorphometric analyses, the rats were subcutaneously injected with calcein green (10 mg/kg) and tetracycline hydrochloride (20 mg/kg; Sigma), respectively, at 13 and 3 days prior to their sacrifice. The left tibia was fixed in 80% ethanol, processed without decalcification, and embedded in modified methylmethacrylate.…”
Section: Bone Turnover and Histomorphometric Analysesmentioning
confidence: 99%
“…No side effects were observed in humans or animals with its regular consumption . Recent studies have shown that genistein supplementation in rats with acute MTX treatment preserved osteogenesis and prevented bone loss and marrow adiposity …”
Section: Potential Strategies For Preventing Methotrexate‐induced Bonmentioning
confidence: 99%